THE PAR (PEER ASSESSMENT RATING) CALCULATION ON 2 DIMENSIONAL TEETH MODEL IMAGE FOR THE CENTERLINE COMPONENT AND TEETH SEGMENTATION ON THE OCCLUSAL SURFACE TEETH MODEL IMAGE - Hanif Arief Wisesa; Ratna Rustamadji; Miesje Karmiati Purwanegara; Benny Hardjono (Jurnal Ilmu Komputer dan Informasi, 2014)
Abstract The PAR (Peer Assessment Rating) Index is used by orthodontists around the world to calculate the severeness of a malocclusion. A malocclusion is a dental disease where the teeth are not properly aligned. In Indonesia, the number of malocclusion is relatively high. The occurrence of orthodontics who can treat malocclusion is also low in Indonesia. In 2013, a research is done to create the telehealth monitoring system to provide better treatment of malocclusion in Indonesia. The research is further improved by using different Adaptive Multiple Thresholding methods to segmentate the image. The result will be used to calculate the Centerline component of the PAR Index. The result is a system that could calculate the PAR Index automatically and is compared to the results using manual method.